2020
DOI: 10.1029/2020gl089934
|View full text |Cite
|
Sign up to set email alerts
|

Poleward Shift of Atmospheric Rivers in the Southern Hemisphere in Recent Decades

Abstract: The atmospheric river (AR) frequency trends over the Southern Hemisphere are investigated using three reanalyses and two Community Earth System Model (CESM) ensembles. The results show that AR frequency has been increasing over the Southern Ocean and decreasing over lower latitudes in the past four decades and that ARs have been shifting poleward. While the observed trends are mostly driven by the poleward shift of the westerly jet, fully coupled CESM experiments indicate anthropogenic forcing would result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 59 publications
6
64
1
Order By: Relevance
“…Here, long-term evolutions mostly involve the latitudinal dimension. Changes in the general circulation and especially the expected meridional shifts of the storm tracks (either driven by increasing greenhouse effect or ozone recovery: e.g., Thompson et al, 2011), low-frequency evolutions in the state of the SAM, and ongoing warming trends, could all modify the intrinsic properties of both regimes and AR events, that is, their recurrence, location (Ma et al, 2020), extension and intensity. Potentially, they could also change their effects on the ice sheet, for example, through stronger extreme precipitation due to Clausius-Clapeyron scaling (Betts & Harshvardhan, 1987;Kharin et al, 2007;Muller et al, 2011;O'Gorman & Schneider, 2009;Pall et al, 2007;Trenberth et al, 2003;Westra et al, 2014), or through enhanced melt occurring under warmer surface air temperatures, especially near the coast (Wille et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Here, long-term evolutions mostly involve the latitudinal dimension. Changes in the general circulation and especially the expected meridional shifts of the storm tracks (either driven by increasing greenhouse effect or ozone recovery: e.g., Thompson et al, 2011), low-frequency evolutions in the state of the SAM, and ongoing warming trends, could all modify the intrinsic properties of both regimes and AR events, that is, their recurrence, location (Ma et al, 2020), extension and intensity. Potentially, they could also change their effects on the ice sheet, for example, through stronger extreme precipitation due to Clausius-Clapeyron scaling (Betts & Harshvardhan, 1987;Kharin et al, 2007;Muller et al, 2011;O'Gorman & Schneider, 2009;Pall et al, 2007;Trenberth et al, 2003;Westra et al, 2014), or through enhanced melt occurring under warmer surface air temperatures, especially near the coast (Wille et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, questions have been raised about how ARs will change in the future climate. AR occurrence is projected to increase (Dettinger, 2011;Lavers et al, 2013;Warner et al, 2015) with longer and wider geometric shapes, stronger intensities, and a poleward shift of landfall locations (Espinoza et al, 2018;Ma et al, 2020;Radic et al, 2015;Shields & Kiehl, 2016). The MJO is projected to have deeper and larger convection and to travel further eastward with increasing phase speed (Adames et al, 2017;Chang et al, 2015;Maloney et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…ARs obtain their high water vapor content from tropical or extratropical moisture sources, moisture convergence, or local evaporation and are often found in the area ahead of the cold front of extratropical cyclones (Rutz et al 2014;Dacre et al 2015). Many studies have shown the global importance of ARs to poleward moisture transport, climate, and water budgets (Zhu and Newell 1998;Guan and Waliser 2017;Paltan et al 2017;Waliser and Guan 2017;Guan et al 2018;Nash et al 2018;Ma et al 2020). Poleward integrated vapor transport (IVT) from ARs makes up over 90% of the total moisture transport in the mid to high latitudes (Zhu and Newell 1998;Guan and Waliser 2015).…”
Section: Introductionmentioning
confidence: 99%